2014
DOI: 10.3348/kjr.2014.15.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Readout-Segmented Echo-Planar Imaging in Diffusion-Weighted MR Imaging in Breast Cancer: Comparison with Single-Shot Echo-Planar Imaging in Image Quality

Abstract: ObjectiveThe purpose of this study was to compare the image quality of standard single-shot echo-planar imaging (ss-EPI) and that of readout-segmented EPI (rs-EPI) in patients with breast cancer.Materials and MethodsSeventy-one patients with 74 breast cancers underwent both ss-EPI and rs-EPI. For qualitative comparison of image quality, three readers independently assessed the two sets of diffusion-weighted (DW) images. To evaluate geometric distortion, a comparison was made between lesion lengths derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
60
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 15 publications
5
60
1
Order By: Relevance
“…Koyasu et al also reported that the distortion in DWI was significantly reduced with rs‐EPI than in ss‐EPI in both phantom and patient studies. The other studies about rs‐EPI of breast imaging demonstrated that rs‐EPI provided higher image quality and lesion conspicuity than ss‐EPI, thus rs‐EPI reached a higher diagnostic accuracy for the differentiation of benign and malignant breast lesions …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Koyasu et al also reported that the distortion in DWI was significantly reduced with rs‐EPI than in ss‐EPI in both phantom and patient studies. The other studies about rs‐EPI of breast imaging demonstrated that rs‐EPI provided higher image quality and lesion conspicuity than ss‐EPI, thus rs‐EPI reached a higher diagnostic accuracy for the differentiation of benign and malignant breast lesions …”
Section: Discussionmentioning
confidence: 96%
“…However, there are techniques currently in use to minimize these drawbacks, such as twice‐refocused sequences to mitigate eddy current induced distortions, and reversed phase encoding techniques to mitigate susceptibility‐induced distortions . Several previous studies evaluated the quantitative and qualitative comparisons of the image quality between ss‐EPI and rs‐EPI . One study about DWI of the pediatric brain reported that rs‐EPI provided improved image quality compared to ss‐EPI .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The less than perfect concordance with DCE MRI, which we set as a reference standard, implies a considerable gap in spatial resolution that needs to be addressed. However, this may be achievable, as several studies have demonstrated a significant improvement in parameters pertaining to image quality when either higher field strength, rs‐EPI, or rFOV techniques were employed . Most notably, Bogner et al indicated that DWI at 7T may enable morphological assessment of breast lesions by offering spatial resolution that is close to the recommendations for DCE MRI …”
Section: Discussionmentioning
confidence: 99%